2020
DOI: 10.21037/jtd-19-3591
|View full text |Cite
|
Sign up to set email alerts
|

The growth feature and its diagnostic value for benign and malignant pulmonary nodules met in routine clinical practice

Abstract: Background: Growth rate is an independent risk factor for lung cancer in screened pulmonary nodules.This study aimed to clarify growth characteristics of pulmonary nodules in routine clinical practice and examine whether volume doubling time (VDT) can predict the malignancy of these nodules. Methods: We retrospectively enrolled patients with 5-30-mm-sized pulmonary nodules that had been surgically resected after a follow-up of at least 3 months. Two follow-up computed tomography (CT) images with similar thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A plenty of previous researches ( 10 , 13 , 24 , 25 ) have clarified that there are different growth patterns in lung cancer, among which some are stable whereas the others grow at fairly steady increments or demonstrated periods of accelerated growth. We presumed it a different case to talk about an increase in size and growth, and there might be other factors apart from growth that would show significant relevance with nodule malignancy and furthermore malignant grading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plenty of previous researches ( 10 , 13 , 24 , 25 ) have clarified that there are different growth patterns in lung cancer, among which some are stable whereas the others grow at fairly steady increments or demonstrated periods of accelerated growth. We presumed it a different case to talk about an increase in size and growth, and there might be other factors apart from growth that would show significant relevance with nodule malignancy and furthermore malignant grading.…”
Section: Discussionmentioning
confidence: 99%
“…In current practice, lung nodules identified by CT are managed according to the widely accepted guidelines that heavily rely on nodule size (4,(6)(7)(8)(9). While recently researchers found that growth rate of nodules (10) and solid portions (11,12) were also the risk factors of lung cancer, Lindell R. M. et al clarified different growing patterns of lung nodules that were then diagnosed as lung cancer at last (13). These indicated that regarding to nodule malignancy, it was far from enough for judgment with only the consideration of nodule size.…”
Section: Introductionmentioning
confidence: 99%
“…However, after studying the pathological findings, it revealed that types I and III SPINs may not grow significantly due to significant fibrous tissue proliferation and hyaline change. Thus, follow-up could provide more information for the likely diagnosis because most of malignant solid nodules will increase in size and/or density, 31 and such information should be added in an affected patient’s flowchart for discriminating SPINs from cancerous nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of a PN refers to an increase in size between two given CT examinations. Nodule growth rate is considered an independent risk factor for LC in screen-detected PN, allegedly the strongest predictor of risk (77). The optimal prediction of the likelihood of LC is granted by longitudinal assessment of VDT (33).…”
Section: Vdtmentioning
confidence: 99%
“…Malignant PN tend to grow rapidly (VDT <400 days) but there are not strict rules. Benign PN might indeed show a rapid growth (VDT <400 days) as well as malignant ones might grow slowly (VDT >400 days) or even remain stable for a considerable period of time (77).…”
Section: Vdtmentioning
confidence: 99%